If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5x + 2 = 4x + 2 Reorder the terms: 2 + 2x + -5x = 4x + 2 Combine like terms: 2x + -5x = -3x 2 + -3x = 4x + 2 Reorder the terms: 2 + -3x = 2 + 4x Add '-2' to each side of the equation. 2 + -2 + -3x = 2 + -2 + 4x Combine like terms: 2 + -2 = 0 0 + -3x = 2 + -2 + 4x -3x = 2 + -2 + 4x Combine like terms: 2 + -2 = 0 -3x = 0 + 4x -3x = 4x Solving -3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3x + -4x = 4x + -4x Combine like terms: -3x + -4x = -7x -7x = 4x + -4x Combine like terms: 4x + -4x = 0 -7x = 0 Divide each side by '-7'. x = 0 Simplifying x = 0
| x-5y+3z=19 | | sec(3x)/2 | | 3(y+2)-2=4 | | f(x)=x(900-9x) | | -3x+2y-z=-20 | | -(3-q)=1/2(6q-26) | | 12-x=x/5 | | -1x+4=11 | | 39=6(c) | | N^2=12+132 | | 4=-2(4t+2) | | 4ax+6ay-4bx-6by= | | N^2=12+144 | | N^2=12+48 | | 4(2m+3)-6=6m+8 | | 1.06666666667= | | 43=3u+13 | | 2(4t-6)=25t+7 | | x+4z=17 | | 5x+50=7x-14 | | 3b^2-4b+6=0 | | -2(6+m)=-16+2m | | 4.5-x=3.5-x | | 5(5x+10)-13x+64=198 | | x^3+16x^2+9x+27=0 | | 5(5x+10)-13x+64=194 | | 12x=4x-88 | | x+x^2=-.25 | | -4y+-5.6-4.4y= | | 9-2m=7+2(m-3) | | 3-[n-1]=-2 | | 3x+2y=1.6 |